Community structure of polypores (Basidiomycota) in Andean alder wood in Argentina: Functional groups among wood-decay fungi? - Urcelay, Roberto Carlos (2004)
The polypores (Aphyllophorales s.l., Basidiomycota) are very effective wood decayers. Different species differ in their capacity to decay wood; therefore, many functionally different species can be found decaying different substrate conditions (decay stages and log diameter). This study aimed to describe the structure of the wood-decay polypore communities that occur on different states of wood of the Andean alder (Alnus acuminata) within Argentina and to identify groups of polypore species that share the same substrate condition, and thus might have a similar functional role in the decay processes. We found 16 polypore species, among which Trametes versicolor, Bjerkandera adusta and Trametes cubensis were dominant species, showing the highest relative frequency in alder wood. Species richness was lower on trunks of living trees and higher on dead branches. Based on preferential occurrence on different wood conditions, a cluster analysis distinguished three groups, each of them containing one of the three dominant species. This corresponds to the situation of other groups of organisms, where each functional type consists of a dominant species that accounts for most of the ‘function’ and several subordinate species with similar functions. Albeit preliminary, our results provide a formal classification of wood-decay fungi into functional types.